2022
DOI: 10.1097/bpo.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Pediatric Septic Arthritis in the United States: A PHIS Database Study

Abstract: Background: The presence of seasonal patterns in pediatric septic arthritis cases is a common orthopaedic teaching. Seasonal variation has been seen in centers outside of the United States and with other inflammatory and infectious joint-related conditions within the country, but it is unknown if a seasonal pattern exists among different regions of the United States. The purpose of this study was to examine the seasonal variation of septic arthritis within specific regions across the United States. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…15 There was also a perceived seasonal variation in the cases of pediatric SA and was often common pediatric orthopaedic teaching, but a recent study using national database of pediatric hospital centers showed no clear seasonal variation in the cases of pediatric SA in the United States. It did however show a seasonal variation within the Northeast region which is most likely related to weather changes 16 …”
Section: Microbiology: a Change In Epidemiological Landscapementioning
confidence: 90%
See 1 more Smart Citation
“…15 There was also a perceived seasonal variation in the cases of pediatric SA and was often common pediatric orthopaedic teaching, but a recent study using national database of pediatric hospital centers showed no clear seasonal variation in the cases of pediatric SA in the United States. It did however show a seasonal variation within the Northeast region which is most likely related to weather changes 16 …”
Section: Microbiology: a Change In Epidemiological Landscapementioning
confidence: 90%
“…It did however show a seasonal variation within the Northeast region which is most likely related to weather changes. 16…”
Section: Microbiology: a Change In Epidemiological Landscapementioning
confidence: 99%
“…Aureus is more resistant to antibiotics than other organisms [8][9][10]. And hip involvement is more likely to cause growth disturbance than other joints [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify the risk factors and clinical features that can help differentiate septic arthritis from other causes of joint inflammation in children. Several studies have investigated these aspects, but the results have been inconsistent and conflicting [8][9][10][11][12]. Some studies have suggested that age younger than 3 years, male sex, previous joint problems or surgery, immunodeficiency, and recent infection or injury are associated with an increased risk of septic arthritis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%